Sonoelectrochemical Synthesis of Antibacterial Active Silver Nanoparticles in Rhamnolipid Solution - Mariana Shepida; Orest Kuntyi; Martyn Sozanskyi; Yuriy Sukhatskiy (Advances in Materials Science and Engineering)
The results of studies of the synthesis of AgNPs colloidal solutions by cyclic voltammetry (E from +1.0 to −1.0 V) in rhamnolipid (RL) solutions and the use of soluble anodes in the ultrasound field (22 kHz) are presented. It is shown that the algorithm of anodic dissolution—reduction of Ag(I)—nucleation, and formation of AgNPs makes it possible to obtain nanoparticles with the size from 1 nm to 3 nm. It was found that with an increase in the RL concentration from 1 g/L to 4 g/L, the anodic and cathodic currents increase as well as the rate of AgNPs formation, respectively. The rate of nanoparticles formation also increases with an increase in temperature from 20°C to 60°C, and it corresponds to the diffusion-kinetic range of action of this factor. Moreover, the size of AgNPs depends little on the temperature. The character of the UV-Vis pattern of AgNPs colloidal solutions in RL (with an absorption maximum of 415 nm) is the same over a wide range of nanoparticle concentrations. The curves practically do not change in time, which indicate the stability of anodic and cathodic processes during prolonged sonoelectrochemical synthesis. The cyclic voltammetry curves practically do not change in time, which indicate the stability of anodic and cathodic processes during prolonged sonoelectrochemical synthesis. The antimicrobial activity of synthesized AgNPs solutions to strains of Escherichia coli, Candida albicans, and Staphylococcus aureus was established.